Tinjauan Fikih dan Tasawuf Terhadap Tirakat dalam Tradisi Jawa - AL FARISI, M. ALAN (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
The Javanese Muslim community today remains closely connected to the legacy of tirakat traditions that have been passed down for centuries as a result of the process of spreading Islam in Java. Tirakat is a traditional phenomenon intertwined with spirituality and religious values, which often gives rise to debates regarding the legality of its practice. This is what has inspired the author to explore and examine how Islamic jurisprudence (fiqh) and Sufism (tasawwuf) view the tirakat tradition that continues to live and thrive in Javanese society. This study employs a literature review method, using library sources as its primary data. The research produces a novelty in the form of Sufi and juridical perspectives on the Javanese tirakat tradition. Tirakat is an act of ascetic discipline closely related to spirituality — an effort to restrain one’s desires by fasting or by secluding oneself in quiet and solitary places such as mountains or caves. The Javanese people recognize many diverse forms of tirakat, which can generally be grouped into three types: tirakat puasa (ascetic fasting), tirakat tapa (meditative seclusion or austerity), and tirakat melek (wakeful vigil or staying awake). In Javanese tradition, tirakat may be practiced as long as it does not contradict Islamic law, does not cause self-harm, and does not lead one to abandon more important obligations.